Atmospheric aging enhances the ice nucleation ability of biomass-burning aerosol - Jahl, Lydia G. (Sci Adv, 2021)
Ice-nucleating particles (INPs) in biomass-burning aerosol (BBA) that affect cloud glaciation, microphysics, precipitation, and radiative forcing were recently found to be driven by the production of mineral phases. BBA experiences extensive chemical aging as the smoke plume dilutes, and we explored how this alters the ice activity of the smoke using simulated atmospheric aging of authentic BBA in a chamber reactor. Unexpectedly, atmospheric aging enhanced the ice activity for most types of fuels and aging schemes. The removal of organic carbon particle coatings that conceal the mineral-based ice-active sites by evaporation or oxidation then dissolution can increase the ice activity by greater than an order of magnitude. This represents a different framework for the evolution of INPs from biomass burning where BBA becomes more ice active as it dilutes and ages, making a larger contribution to the INP budget, resulting cloud microphysics, and climate forcing than is currently considered.